Politics, Ideology, and Literary Discourse in Modern China : Theoretical Interventions and Cultural Critique - Tang, Xiaobing, 1964-; Liu, Kang, 1955- (Book collections on Project MUSE., 1993)
This collection of essays addresses the perception that our understanding of modern China will be enhanced by opening the literature of China to more rigorous theoretical and comparative study. In doing so, the book confronts the problematic and complex subject of China's literary, theoretical, and cultural responses to the experience of the modern. With chapters by writers, scholars, and critics from mainland China, Hong Kong, and the United States, this volume explores the complexity of representing modernity within the Chinese context. Addressing the problem of finding a proper language for.